(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article medicine in the field digital transformation Big Data analysis in the process and other modern technologies ( artificial intelligence , blockchain , telemedicine ) replace learns . Home attention this of technologies health storage systems efficiency increase , expenses optimization and state from funds reasonable to use add to the extent The article is focused on In Uzbekistan current being done digitization initiatives and international experiments analysis Research results this The data shows that based on decision acceptance to do , processes automation and resources clear management through good quality medical service to show provide with together financial savings done increase possible .